Is There Excess Capacity Really? - Tamara Todorova (Theoretical and Practical Research in Economic Fields, 2015)
Excess capacity is viewed as a distinctive feature and an essential inefficiency of monopolistic competition as the large-group case of imperfect competition. Using a simple geometrical approach and studying the demand and cost curves faced by the individual firm, we find that there is little potential for excess capacity in monopolistically competitive markets, opposite to the common perception and wide coverage in the literature. We see monopolistic competition as the true type of competition in the presence of transaction costs where perfect competition is a hypothetical and ideal benchmark which cannot exist under positive transaction costs.
Keywords: D23; D24; D43; L13; 330; excess capacity; monopolistic competition; oligopoly; transaction costs